Methodological Approaches Tomanagingrelationships with Consumers - Musayeva Shoira Azimovna; Usmanov Farzod Shokhrukhovich (Research Parks Publishers, 2022)
The article analyzes the criteria for identifying a profitable client, provides effective ways to assess customer loyalty, as well as methods for calculating the value of a customer base for a company. It is concluded that it is necessary to apply an integrated approach to studying the loyalty of the company's customers.